2021
DOI: 10.1108/jima-04-2020-0100
|View full text |Cite
|
Sign up to set email alerts
|

Salesperson ethics behavior as antecedent of Islamic banking customer loyalty

Abstract: Purpose The development of the banking industry is encouraging increasingly fierce competition. In the face of banking competition, Islamic banks need to build customer loyalty by paying attention to ethical aspects. Ethics has an essential role in forming and preserve relationships between companies and customers in the long term. The measurement model of salesperson ethical behavior in this study was built using the Islamic-based marketing concept. This study aims to test empirical models of Islamic ethics-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(54 citation statements)
references
References 44 publications
6
48
0
Order By: Relevance
“…The result is also supported by Zeithaml and Bitner (2003), who state that the quality of the relationship between the customer and the service provider is a key element in the formation of customer loyalty. Furthermore, the result is consistent with the findings of prior research in various service industries (Liu et al, 2011;Rahman and Ramli, 2016) and in Islamic banking (Wijaya et al, 2021) that confirmed the influence of relationship quality on customer loyalty.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The result is also supported by Zeithaml and Bitner (2003), who state that the quality of the relationship between the customer and the service provider is a key element in the formation of customer loyalty. Furthermore, the result is consistent with the findings of prior research in various service industries (Liu et al, 2011;Rahman and Ramli, 2016) and in Islamic banking (Wijaya et al, 2021) that confirmed the influence of relationship quality on customer loyalty.…”
Section: Discussionsupporting
confidence: 90%
“…The results imply that customer loyalty to an Islamic bank is associated with relationship quality, service quality and customer satisfaction. These results are in line with previous studies, which have reported positive and significant relationships between these variables (Amin et al, 2011;Aydin and Ozer, 2005;Caruana, 2002;Wijaya et al, 2021;Wu et al, 2019).…”
Section: Descriptive Statisticssupporting
confidence: 93%
See 3 more Smart Citations